The beginning of philological education at the Belarusian State University - Zuyeva, Olga V. (Journal of the Belarusian State University. Philology, 2021)
The preparatory and initial stages of the work of scientists and organisers of science to provide professional philological training at the Belarusian State University are characterised. The dependence of the content of linguistic and literary courses and teaching methods in the early years of the university on external, primarily economic factors is shown. The social structure of the first students of the ethnological and linguistic department of the Belarusian State University is indicated.
Keywords: Belarusian State University; philology; ethnological and linguistic department; 1921; language; literature